PENGARUH KEDATANGAN PENERBANGAN DENGAN TINGKAT HUNIAN HOTEL DI PROVINSI KEPULAUAN BANGKA BELITUNG. - utama, Atpriatna; Prabu, Ngadimun (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
This research study to see whether there is a significant relationship between Flight Arrival with Hotel occupancy rate in the province of Bangka Belitung islands. The methods used through the Quantitative Approach. Data analysis used consist of statistical data of Analytical and Analytical Statistics which sourced from Central Bureau of Statistics of Province of Bangka Belitung Islands in 2012 -2016. The results of the study show that the Flight Arrival shows a strong relationship and in line with the hotel occupancy rate in the province of bangka belitung island with the coefficient value of 0.56.   Keyword. Flight Arrival, Hotel Occupancy Rate.